Implementation of Community-Based Islamic Religious Education in Binjai City - Vira Regina Cahyani; Afrahul Fadhila Daulai; Humaidah Br. Hasibuan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This research, entitled "Implementation of Community-Based Islamic Religious Education in Binjai City," is motivated by the low level of implementation of Islamic Religious Education in the worship aspect of Binjai City, as seen from the understanding and implementation of daily worship, such as prayer, both in the mosque and prayer room. The purpose of this study is to determine the implementation of community-based Islamic Religious Education in the worship aspect, and the supporting and inhibiting factors. This research method is qualitative. The research instrument is interviews. The analysis technique uses an interactive model in the form of data reduction, data presentation, and drawing conclusions. The research findings are that the implementation of community-based Islamic Religious Education on the aspect of worship in Binjai City emphasizes the role of community elements, namely the MUI of Binjai City, Islamic Religious Figures in Binjai City and the Muslim Community of Binjai City through community consultation services, Daurah Fiqh, and Higher Education for Ulama Cadres (PTKU), regular religious studies, congregational prayer movements in Mosques and worship practices. Supporting factors are the Synergy of the Three Pillars (Ulama, Umara and Umat), the religious character of the community, strong determination from individual communities, family factors, environmental factors, consistent Ustadz, and the active role of BKM. The inhibiting factors are the quality of some educators who are not yet optimal, partial understanding of some communities, cultures that are contrary to sharia, shame in some Muslim communities, low religious literacy, lack of ustadz in the area, and also the problem of activity time.